Improving the participation of adults with visual and severe or profound intellectual disabilities: a process evaluation of a new intervention - Gineke Hanzen; Ruth M. A. van Nispen; Carla Vlaskamp; Eliza L. Korevaar; Aly Waninge; Annette A. J. van der Putten (BMC, 2020)
Abstract Background While the participation of adults with visual and severe or profound intellectual disabilities (VSPID) in society and community life is important, evidence-based interventions to improve their participation are lacking. We conducted a process evaluation of the implementation of 'Care for Participation+' (CFP+), a new intervention targeting the attitudes of direct support professionals (DSPs) toward the participation of adults with VSPID, within a residential facility in the Netherlands. Methods CFP+ was inspired by the Boston Psychiatric Rehabilitation Approach and adapted by adopting a new definition and operationalization of the concept of participation for adults with VSPID. Following systematic training, 16 DSPs of adults with VSPID were able to apply key elements of CFP+ to explore diverse roles and activities for this population, facilitating their self-management, teaching them necessary skills for participation, and organizing support. Our process evaluation entailed an investigation of the delivered dose, reach, fidelity, and adaptation of CFP+ during and after the CFP+ intervention. We also evaluated the mechanisms of impact and context using questionnaires, assignments, documentation, interviews, and a logbook. Results The intended dose, reach, and fidelity relating to the implementation of CFP+ were not achieved. Despite this fact, an assessment of the mechanisms of impact indicated that assignments of CFP+ were well (75%) or reasonably well (17%) understood by DSPs. CFP+ was applied by DSPs to stimulate self-management (83% of DSPs), new activities (100%), enhanced involvement in existing activities (67%) and to explore new roles (50%) for adults with VSPID. A negative contextual factor mentioned by the trainer and manager was the DSPs' lack of commitment to the training program. Another negative contextual factor mentioned by DSPs was the lack of time for implementing CFP+. Conclusions CFP+ provides new opportunities to improve the participation of adults with VSPID. Despite the non-optimal conditions for implementing CFP+ and the DSPs' general reluctance to apply the new intervention, some have actively used CFP+ within the residential facility. Future studies should focus on the outcomes of CFP+ regarding attitudinal changes among DSPs relating to the participation of adults with VSPID and their quality of life.